A self-reported questionnaire for screening of hearing impairment in older - Mishra Aakash; Nanavati Nikita (The Egyptian Journal of Otolaryngology)
Abstract Introduction Hearing loss is a prevalent concern for older adults aged 60 years and above, making early intervention essential. Accurate diagnosis relies on calibrated instruments, soundproof environments, and qualified audiologists. While these resources are often available, certain situations may limit access. This study investigates the potential of self-assessment tools as an alternative screening method for older adults to identify those who may require further audiological evaluation. Aim To study the efficacy of self-reported questionnaire in identifying hearing loss among older adults and its potential application in clinical practice. Method This cross-sectional study included a total of 160 older adults. Participants were divided into two groups: Group I with normal hearing sensitivity and Group II with mild to moderately severe sensorineural hearing loss. Pure-tone audiometry was used to measure hearing thresholds, followed by administering a questionnaire. Result It was observed that there was significant difference between scores of the self-awareness and communication difficulties for different degrees of hearing loss among older adults (p-value < 0.05). The cut-off score was observed to be increasing with the increase of the hearing loss, and also, it was observed that there is a positive strong correlation between scores of self-awareness domain and communication difficulties domain across different degrees of hearing loss. Conclusion Thus, this questionnaire could be an effective tool for screening of hearing loss and assessing its severity, from mild to moderately severe in older adults. This will facilitate early detection and intervention, potentially enhancing their quality of life.